Association of Depression Onset and Treatment With Blood Pressure Control After Intracerebral Hemorrhage. Issue 1 (29th November 2022) - Keins, Sophia; Abramson, Jessica R.; Mallick, Akashleena; Pablo Castello, Juan; Rodriguez-Torres, Axana; Popescu, Dominique; Hoffman, Danielle; Kourkoulis, Christina; Gurol, M. Edip; Greenberg, Steven M.; Anderson, Christopher D.; Viswanathan, Anand; et al.
Abstract : Background: Blood pressure (BP) control represents a crucial intervention to improve long-term outcomes following spontaneous intracerebral hemorrhage (ICH). However, fewer than half of ICH survivors achieve target treatment goals. ICH survivors are also at very high risk for poststroke depression, which may contribute to inadequate BP control. We, therefore, sought to determine whether depressive symptoms after ICH are associated with inadequate BP control. We also investigated whether associations between depression after ICH and BP measurements were mediated by treatment with selective serotonin reuptake inhibitors or norepinephrine-serotonin reuptake inhibitors antidepressants. Methods: We leveraged data from a single-center longitudinal study of ICH conducted at Massachusetts General Hospital (Boston, MA) between 2006 and 2018. We collected data from semiautomated review of electronic health records, baseline and follow-up interviews, and computed tomography imaging. Information on BP measurements, depression diagnoses, antidepressants medication use, and medical visits were collected longitudinally and analyzed using mixed effects models. Primary outcomes included systolic and diastolic BP measurements during long-term follow-up after ICH. Results: We included 1243 consecutive ICH patients without pre-stroke depression history. Of these, 721 (58%) were diagnosed with incident depression over a median follow-up time of 52.8 months (interquartile range, 42.1–60.5). Depression onset was associated with subsequent increase in systolic (+8.3 mm Hg, SE, 2.4 mm Hg, P =0.012) and diastolic (+4.4 mm Hg, SE, 1.2 mm Hg) BP measurements. Resolution of depressive symptoms was associated with subsequent decrease in systolic (−5.9 mm Hg, SE, 1.4 mm Hg, P =0.031) and diastolic (−3.4 mm Hg, SE, 1.1 mm Hg, P =0.041) BP measurements. We also found associations between higher systolic BP measurements and use of selective serotonin reuptake inhibitor and noradrenaline-serotonin reuptake inhibitor antidepressants, independent of whether depression symptoms were active or not (all P <0.05). Conclusions: ICH survivors displayed increasing BP values after receiving a diagnosis of depression, followed by decreasing values among those experiencing resolution of depressive symptoms. Use of selective serotonin reuptake inhibitor and noradrenaline-serotonin reuptake inhibitor antidepressants was independently associated with higher systolic BP measurements. Clinicians ought to closely monitor BP for ICH survivors being treated for depression, especially using selective serotonin reuptake inhibitor and noradrenaline-serotonin reuptake inhibitor. Future studies will also be required to investigate the mechanisms underlying these associations.